On Social Tolerance and the Evolution of Human Normative Guidance. (5th October 2017) - Gonzalez-Cabrera, Ivan
Abstract: Discussions about the evolution of human social cognition usually portray the social environment of early hominins as highly hierarchical and violent. In this evolutionary narrative, our propensity for violence was overcome in our lineage by an increase in our intellectual capacities. However, I will argue in this article that we are at least equally justified in believing that our early hominin ancestors were less aggressive and hierarchical than is suggested in these models. This view is consistent with the available comparative and palaeoanthropological evidence. I will show that this alternative model not only does not support long-held views of human origins, but also has important consequences for debates about the evolution of our capacity for normative guidance. 1 Introduction 2 Philosophical Motivation 3 The Puzzle of Hominin Evolution 4 The Mosaic Hypothesis 5 Evidence for the Model 6 Palaeoanthropological Support 7 Philosophical Consequences